2019
DOI: 10.1002/ejoc.201801763
|View full text |Cite
|
Sign up to set email alerts
|

Aziridination of Aromatic Aldimines Through Stabilized Ammonium Ylides: A Molecular Electron Density Theory Study

Abstract: The domino reaction between ammonium salt AS 4 and aldimine AD 2, in the presence of Cs2CO3, yielding aziridine trans‐AZ 7 was studied within the Molecular Electron Density Theory at the B3LYP (PCM, DCM)/def2‐TZVP//B3LYP (PCM, DCM)/GenECP computational level. This domino reaction begins with the proton abstraction from AS 4 by Cs2CO3 yielding ammonium ylide AY 5. The subsequent nucleophilic attack of AY 5 on AD 2 furnishes the gauche betaine‐like intermediate IN‐2Tg1, which experiences a C–C single bond rotati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…It should also be pointed out that, similar to the trans pathway, the ring closure step is the RDS within the cis pathway. Note, however, that in the aziridination reaction recently studied by Emamian and coworkers , the RDS is the ring closure step.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should also be pointed out that, similar to the trans pathway, the ring closure step is the RDS within the cis pathway. Note, however, that in the aziridination reaction recently studied by Emamian and coworkers , the RDS is the ring closure step.…”
Section: Resultsmentioning
confidence: 99%
“…There are few theoretical studies on aziridination reaction that have fully studied energy transformation, selectivities, and mechanistic aspects. Very recently, Emamian and coworkers reported a molecular electron density theory (MEDT) study on the stereoselective aziridination of aromatic aldimines through stabilized ammonium ylides. This investigation demonstrated that the reaction under study takes place at highly trans ‐stereoselectivity, in excellent agreement with experimentally findings , and the ring closer step is the rate‐determining step (RDS).…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Emamian et al reported a molecular electron density theory (MEDT) study to analyze stereoselective aziridination of aromatic aldimines through stabilized ammonium ylides. Their investigation showed that the reaction under study progress at highly trans ‐stereoselectivity, in excellent agreement with experimentally findings, and its ring closer step is the rate‐determining step (RDS).…”
Section: Introductionmentioning
confidence: 99%